2013
DOI: 10.4161/chan.26100
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of potassium channels in pancreatic duct epithelial cells

Abstract: Potassium channels regulate excitability, epithelial ion transport, proliferation, and apoptosis. In pancreatic ducts, K+ channels hyperpolarize the membrane potential and provide the driving force for anion secretion. This review focuses on the molecular candidates of functional K+ channels in pancreatic duct cells, including KCNN4 (KCa3.1), KCNMA1 (KCa1.1), KCNQ1 (Kv7.1), KCNH2 (Kv11.1), KCNH5 (Kv10.2), KCNT1 (KCa4.1), KCNT2 (KCa4.2), and KCNK5 (K2P5.1). We will give an overview of K+ channels with respect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 146 publications
1
35
0
Order By: Relevance
“…Furthermore, luminal K + channels could contribute to secreted K + , as pancreatic juice contains 4–8 mM K + (Sewell and Young, 1975; Caflisch et al, 1979; Seow et al, 1991). The molecular identity of some K + channels in pancreatic ducts is known, however, the exact localization and function remains to be verified [see (Hayashi and Novak, 2013)]. The K Ca 1.1 channels (maxi-K, BK, coded by KCNMA1 ) are present in pancreatic ducts (Hede et al, 2005; Venglovecz et al, 2011).…”
Section: Novel Ion Channels and Pumps Contributing To Acid-base Transmentioning
confidence: 99%
“…Furthermore, luminal K + channels could contribute to secreted K + , as pancreatic juice contains 4–8 mM K + (Sewell and Young, 1975; Caflisch et al, 1979; Seow et al, 1991). The molecular identity of some K + channels in pancreatic ducts is known, however, the exact localization and function remains to be verified [see (Hayashi and Novak, 2013)]. The K Ca 1.1 channels (maxi-K, BK, coded by KCNMA1 ) are present in pancreatic ducts (Hede et al, 2005; Venglovecz et al, 2011).…”
Section: Novel Ion Channels and Pumps Contributing To Acid-base Transmentioning
confidence: 99%
“…More than 30 years ago, the existence of native sodium‐activated potassium currents was demonstrated through electrophysiological experiments in guinea pig cardiomyocytes (Kameyama et al, ). Since then, the presence of native sodium‐activated potassium channels has been reported in diverse myocytes (Kim et al, ; Re et al, ), pancreatic duct epithelial cells (Hayashi and Novak, ), thick ascending limb of Henle's loop in the kidney (Paulais et al, ), various mammalian neurons (Egan et al, ; Kaczmarek, ), and Xenopus oocytes (Egan et al, ). At present, two distinct ion channels giving rise to an outward rectifying potassium current activated upon rises in internal sodium ions have been described (Bhattacharjee and Kaczmarek, ; Salkoff et al, ; Yuan et al, ).…”
mentioning
confidence: 99%
“…An electrophysiological study indicated that KCNK5 was expressed in human pancreatic ductal adenocarcinoma cell line, and the pH-sensitive K2P subunits coded by KCNK5 were shown to be expressed in pancreatic. 20 Transcriptome-wide association study analysis identified several novel candidate genes for PC, such as RP11-65J3.1, PPFIBP2, GEMIN4, NIPA2,RNASEH2B, FARS2, MTHFD1L, F2R, TXNDC15, NDUFA3, CRISPLD2, IQSEC3, and LRP5L. As is known to all, few efforts have been paid to investigate the potential roles of them in the formation of PC.…”
Section: Discussionmentioning
confidence: 99%